(untitled) - Hales, Jonathan A. (Burlington, MA, 2005)
The book offers a clear introduction to fundamental accounting concepts and provides the tools to produce solid financial analysis and optimal operational performance in hotels and restaurants. The text examines the current practices of some of today's leading hotel and restaurant companies and introduces the fundamentals of hospitality accounting from a practical, applied perspective with real industry examples.
Keywords: Hospitality industry; Accounting